(untitled) (REMUNOM, 2025)
Introduction: teenage pregnancy is a multifactorial issue with pathological and psychological repercussions for the mother and fetus; social and financial, for the family involved, and economic, for the healthcare system. Objectives: identify the obstacles encountered in reducing teenage pregnancy rates in Brazil and analyze the governmental policies and actions developed for the healthcare and education system to address them. Methodology: integrative literature review study. Data was collected from the PubMed, Scielo, Lilacs and CAPES Periodicals databases, from August to September 2023, based on pre-established inclusion criteria. The final sample consisted of 13 articles. Results: several obstacles responsible for the current panorama of high incidence of teenage pregnancy were identified, which can be divided into the categories related to the UBS (Unidade Básica de Saúde), the adolescents, the approach of professionals and society. The proposed actions are geared towards each of these factors and their main focus is on more effective and comprehensive sexual education for adolescents, also including social, political and economic issues. Conclusion: the studies evaluated showed success in adopting measures that bring adolescents closer to the health system and its professionals. Also, continuing education measures in schools involving several different educational approaches showed a positive impact. In addition, addressing the social aspect around this topic proved to be of utmost importance in increasing the effectiveness of the proposed actions to reduce the number of cases of teenage pregnancy in Brazil.